1995
DOI: 10.3109/02841869509094014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of C-ERBB-2 Related Protein in Sera from Breast Cancer Patients Relationship to ERBB2 gene amplification and c-erbB-2 protein overexpression in tumour

Abstract: The level of a c-erbB-2 related protein was determined in sera from 168 breast carcinoma patients, 12 females with benign breast disease, and 66 female controls using an ELISA (enzyme linked immunosorbent assay) kit. Elevated c-erbB-2 related protein level was detected in one of 13 preoperative sera (8%), two of 62 postoperative sera from patients without recurrent disease (3%), and 55 of 93 sera collected at recurrent disease (59%). Elevated serum levels were detected significantly more often in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
26
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 25 publications
9
26
0
1
Order By: Relevance
“…Therefore, the availability of a reliable method for measuring circulating levels of HER-2/neu ECD is an interesting opportunity to assess the diagnostic and prognostic role of HER-2/neu overexpression in patients with tumor that are not easily accessible for biopsy. Elevated serum levels of HER-2/neu protein have been correlated with HER-2/neu gene amplification and tissue overexpression in patients with breast carcinoma 26 and gastric carcinoma. 39 In addition, in patients with advanced breast carcinoma, elevated pretreatment levels of the protein were associated with a shorter time to disease progression and overall survival duration, whereas low pretreatment levels were the most powerful predictor of response to hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the availability of a reliable method for measuring circulating levels of HER-2/neu ECD is an interesting opportunity to assess the diagnostic and prognostic role of HER-2/neu overexpression in patients with tumor that are not easily accessible for biopsy. Elevated serum levels of HER-2/neu protein have been correlated with HER-2/neu gene amplification and tissue overexpression in patients with breast carcinoma 26 and gastric carcinoma. 39 In addition, in patients with advanced breast carcinoma, elevated pretreatment levels of the protein were associated with a shorter time to disease progression and overall survival duration, whereas low pretreatment levels were the most powerful predictor of response to hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…24 In some patients, elevated protein serum levels also were detectable prior to the time of clinical diagnosis. 25 High HER-2/neu oncoprotein circulating levels have been correlated with tissue overexpression 26,27 and have been associated with a poor survival outcome in patients with breast carcinoma. 28 -30 A study that considered a heterogeneous group of lung adenocarcinomas also found a good correlation between HER-2/neu expression in tissue and serum levels.…”
mentioning
confidence: 99%
“…These results are similar to outcomes of studies showing that changes in HER-2 overexpression do not correlate with clinical outcome. [17][18][19][20] Chemotherapy and cytokine treatments used to mobilise haematopoietic stem cells into blood can also mobilise tumour cells and the observed increase in the number of patients with circulating HER-2 after ICT may be related to this effect. 30,31 ICT may also increase the amount of soluble HER-2 fragment released from tumours containing HER-2 overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Although HER-2 oncoprotein overexpression correlates with reduced patient survival, few studies have evaluated the incidence of HER-2 overexpression in patients with metastatic breast cancer (MBC) and examined whether increased levels of this protein indicate a poorer prognosis and/or reduced responsiveness to systemic treatment. [14][15][16][17][18][19][20][21][22][23][24] In these studies, 30-50% of patients with MBC had elevated levels of circulating (plasma, serum) extracellular domain of HER-2. [14][15][16][17][18][19] Overexpression correlates with an increased tumour burden and reduced survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation